Designing and Performance Test of Ceramic Furnace Spiral Tube with Solid Fuel - Ahmad, Ary Mustofa (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
The objective of this research was to design and to test the performance of furnace heater that was made from ceramic with solid-fuel and with a spiral tube as a medium for heat transfer. The use of ceramic was aimed to prevent heat loss, and the use of spiral tube as a medium for heat transfer was to increase the contact surface. Performance test was done to include parameters such as calorific value of fuel, heat loss, thermal efficiency, furnace efficiency, and efficiency of fuel used. The test was conducted using two types of fuel as treatment, namely wood charcoal and coal briquettes, and with three times of replication for each treatment and test parameters. The test results indicated that the performance of the furnace using coal briquettes was better than using wood charcoal. The furnace thermal efficiency was 30% and the fuel consumption percentage was 97.44%Keywords : ceramics furnace, spiral tube, heat transfer, solid fuel